Ultrasonographic and electrophysiological outcomes of carpal tunnel syndrome treated with low-level laser therapy: A double-blind, prospective, randomized, sham-controlled study - Merve Nalbant,; Oya Ümit Yemişci,; Selin Özen,; Şehnaz Tezcan, (Archives of Rheumatology, 2022)
Objectives: The aim of this study was to investigate the therapeutic effects of low-level laser therapy (LLLT) on clinical, ultrasonographic (US), and electrophysiological findings in carpal tunnel syndrome (CTS). Patients and methods: Between January 2015 and August 2015, 42 patients (7 males, 35 females; mean age: 50.4±8.7 years; range, 32 to 65 years) with mild-to-moderate CTS were randomly assigned to one of two groups: active LLLT (therapy group, n=22) 0.8 J/painful point and sham LLLT groups (n=20). Both groups wore neutral wrist orthoses. The patients were evaluated before and after 15 sessions of therapy (670 nm, 4 J/session over the carpal tunnel). Follow-up parameters included the Boston Carpal Tunnel Syndrome Questionnaire (BCTQ) Symptom Severity Scale (SSS), Functional Status Scale (FSS), nerve conduction studies and US evaluation of the median nerve cross-sectional area (CSA), vascularization (via power Doppler), flattening ratio (FR), and palmar bowing of the flexor retinaculum. Results: Nocturnal paresthesia improved in both groups; however, pain and patients with a positive Phalen’s test reduced only in the therapy group (p=0.031). The FSS and SSS scores also improved only in the therapy group (p<0.001). Electrophysiologically, median sensory nerve conduction velocities showed a significant improvement only in the therapy group (p=0.002). The CSA, FR, and vascularization of the median nerve showed a significant improvement in the therapy group alone (p<0.001, p=0.048, and p=0.021, respectively). Conclusion: Improvements in the signs and symptoms of CTS and hand function, the improvements in sensory nerve conduction studies, and reduction in median nerve CSA, FR and vascularity in the LLLT group can be attributed to the anti-inflammatory and analgesic effects of LLLT. This study provides new US data demonstrating efficacy of LLLT along with a clinical and electrophysiological improvement. The LLLT seems to be an easily applied, non-invasive treatment option.